The Association between Heat Exposure and Hydration Status Among Production Workers in Fish Processing Company - Tenny Sutarto; Dewi S Soemarko; Slamet Ichsan (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Hot work environment can cause various subjective and objective complaints for workers. When workers perform activities under hot work environment, their body will react by balancing the amount of heat received by the body from outside the body and the loss of water in the body. Hydration status is the condition achieving the balance between water intake and water discharge from the body. Bad hydration status or de-hydration can cause various changes in the body physiological functions. This study was intended to see the association between heat exposure and hydration among production workers in Fish Processing Company Sawangan, Depok.Method : A cross sectional study with 88 respondents, selected as a total sampling. The study was conducted on November 2017 until January 2018. Data analysis were used by SPSS version 20.0.Result: There is no significant difference between the specific gravity of urine before and after working (p=0.076). However, 37.5% of the workers had dehydration. There is a significant association between the work environment temperature and hydration status (p=0.002), and also between water intake and status of hydration (p=0.013). Work environment temperature is the most dominant risk factor to influence dehydration (p=0.000; OR= 9.305; 95%CI=2.727-31.748)Conclusions: There is a significant association between heat exposure and hydration status (p=0.000; OR=9.305). The number of workers that were exposed to heat and experienced dehydration is 33 people (37.5%). Water intake turns to be the individual factor that influences the status of hydration of the workers exposed to heat. The work factor that influences the hydration status of the workers is the work environment temperature.